Magnesium Salt, a Simple Strategy to Improve Methadone Analgesia in Chronic Pain: An Isobolographic Preclinical Study in Neuropathic Mice - González, Valeria; Pelissier, Teresa; Cazanga, Victoria; Hernández, Alejandro; Constandil, Luis (Frontiers in Pharmacology, 2020)
Analgesic efficacy of methadone in cancer and chronic non-cancer pains is greater than that of other opioids, probably because of its unique pharmacokinetics properties and also because it targets glutamatergic receptors in addition to -opioid receptors. However, methadone has drawbacks which are clearly related to dosing and treatment duration. The authors hypothesized that the antinociceptive efficacy of methadone could be synergistically potentiated by magnesium and copper salts in a preclinical mouse model of chronic pain, using the intraplantar formalin test as algesimetric tool. The spared nerve injury mice model was used to generate mononeuropathy. A low dose (0.25%) formalin was injected in the neuropathic limb in order to give rise only to Phase I response, resulting from direct activation by formalin of nociceptive primary afferents. Licking/biting of the formalin-injected limb was evaluated as nociceptive behavior during a 35-min observation period. Dose-response curves for intraperitoneal magnesium sulfate (3, 10, 30 and 100 mg/kg i.p.), copper sulfate (0.1, 0.3, 1 and 3 mg/kg i.p.) and methadone (0.1, 0.3, 3 and 10 mg/kg i.p.) allowed to combine them in equieffective doses and to determine their interaction by isobolographic analysis. Magnesium sulfate, copper sulfate and methadone dose-dependently decreased the nociceptive response evoked by formalin injection, the respective ED50 being 76.38, 1.18 and 0.50 mg/kg i.p. Isobolographic analysis showed a superadditive interaction for magnesium and methadone. Indeed, despite that both ED50 are obviously equieffective, the ED50 for the MgSO4/methadone combination contained less than one third of the methadone having the ED50 for methadone alone. For the CuSO4/methadone combination, the interaction was only additive. Extrapolated to clinical settings, the results suggest that magnesium salts might be used to improve synergistically the efficacy of methadone in neuropathy, which would allow to reduce the dose of methadone and its associated side effects.